Инструктор, тренер, Сифу, тренер или професор? - Размишљања о употреби терминологије у полицијским поставкама за учење које се баве управљањем физичким сукобима - Staller, Mario; Koerner, Swen (NBP. Nauka, bezbednost, policija, 2021)
Police training and learning settings focusing on physical conflict management skills regularly comprise at least two parties: on the one side individuals learning and developing their conflict management skills and on the other side individuals in charge of planning and delivering the training sessions. While the first category refers to learners the latter category is referred to among others as instructor, trainer, coach, sifu or professor depending on contextual constraints. While it seems arbitrary to use different terms for describing the learner’s counterpart in a learning setting, we argue for a sensible consideration of manifest and latent implications of how these individuals are referred to – and how they perceive their role. Drawing from autoethnographic data in various conflict management training settings we identify functional, dysfunctional and irritating aspects of different used terms. By reflecting through the lenses of functionality from a systemic perspective (Luhmann, 2017), we aim at providing insights towards a more nuanced understanding of contextual constraints and reflexive use of these terms.